PARASITISASI Diadegma semiclausum Hellen (HYMENOPTERA: ICHNEUMONIDAE) TERHADAP HAMA Plutella xylostella Linn. (LEPIDOPTERA: YPONOMEUTIDAE) PADA TANAMAN KUBIS DI DESA RURUKAN DAN KAKASKASEN II KOTA TOMOHON - Rifal O. Manopo; Caroulus S. Rante; Mouwy Dien (COCOS, 2018)
ABSTRACT  The research aimed to determine the parasitization of D. semiclausum against P. xylostella in cabbage plants in Rurukan and Kakaskasen II Village, Tomohon City.  The research lasts for five months, from October 2018 to February 2019.  The study used a survey method that was carried out directly on farmers' cabbage plants.  Determining the location of collecting pupa samples is done by purporsive sampling, which is taking samples where there are cabbage plants in both locations, namely Rurukan and Kakaskasen II Village.  Sampling for observation of the percentage of parasitization was carried out directly, namely by taking pupae in the cabbage crop. Samples were placed in used container containers and covered with azahi cloth and then taken to the Entomology and Plant Pest Laboratory, the Sam Ratulangi University of Agriculture Faculty of Manado to be maintained and observed every day.  The results showed that the parasitization of D. semiclausum against pests of P. xylostella in Rurukan and Kakaskasen II villages was 25.57% and 24.76% respectively.  Keywords :  Cabbage plant, Plutella xylostella, Diadegma semiclausum